Peluang dan Tantangan Bank Syariah di Indonesia Dalam Mempertahankan Eksistensi di Era Digital - Junet Andi Setiawan; Mugiyati Mugiyati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to describe the opportunities and challenges of Islamic banks in maintaining their existence in the digital era. The research method used is literature study, by compiling relevant data which is then analyzed using a descriptive approach. The results of the study show that the digital era has provided very promising opportunities for the advancement of the world of Islamic banking, this is because the majority of Indonesian people are Muslim and are supported by many internet users in Indonesia, then the digital era also makes it easier for Islamic banking to promote its products. In addition, Islamic banking also faces the challenge of having to present qualified and competent human resources, guaranteeing protection for its customers, and the most important challenge in facing this digital era is building Cyber ​​Security that is not easy to hack, skiming and safe from malware attacks. Then, in order to maintain its existence in the digital era, Islamic banking has presented a strategy by innovating digital finance by providing good service to its customers, through digital banking such as phone banking, internet banking, SMS banking, and mobile banking. Keywords: Islamic bank, Opportunities, Challenges.